Religiusitas sebagai Moderasi Pengaruh Pendidikan, Pendapatan dan Kesadaran Terhadap Minat Masyarakat Membayar Zakat - Shulhah Nurullaily; Intan Qurratul Aini; Ahmad Nahidl Silmy (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Zakat has a very large potential to improve the economy of Muslims. The economic potential of Muslims cannot be separated from zakat, because zakat is one of the pillars (rukun) in Islam which is closely related to economic factors. This study aims to determine religiosity as a moderation of the influence of education, income and awareness on people's interest in paying zakat. The current analysis uses a quantitative approach. The population of this study is muzakki who have paid zakat. The sample was taken from the population, and the selection of this study sample was determined by random sampling to produce a sample of 150 respondents. The results of this study found that education, income and awareness influence people's interest in paying zakat. Religiosity as a moderation is able to moderate the influence of income and awareness of people's interest in paying zakat. However, religiosity is unable to moderate the influence of education on interest in paying zakat.